2014
DOI: 10.1155/2014/864780
|View full text |Cite
|
Sign up to set email alerts
|

Motor Responses and Weight Gaining in Neonates through Use of Two Methods of Earmuff and Receiving Silence in NICU

Abstract: Background and Aims. With technological advances in NICUs the survival rate of preterm infants has been increased. Because NICU environment is a potent source of stress for infants, its modification is an essential measure to decrease infants' morbidity. The purposes of this study were to compare the effects of wearing earmuff and provision silence for infants on their motor responses and gaining weight. Methods. In a randomized clinical trial 96 preterm infants were enrolled. Their motor responses were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Reducing noise levels for the preterm infant may have important health benefits. Studies of ear covers and ear plugs have shown that noise reduction can improve medical outcomes for preterm infants [13,[37][38][39][40]. There is a concern that the adhesives required to keep ear covers on the skin of the infant are responsible for breakdown of the fragile skin of the patient [41] and that they decrease all auditory input including the directed communication needed for…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Reducing noise levels for the preterm infant may have important health benefits. Studies of ear covers and ear plugs have shown that noise reduction can improve medical outcomes for preterm infants [13,[37][38][39][40]. There is a concern that the adhesives required to keep ear covers on the skin of the infant are responsible for breakdown of the fragile skin of the patient [41] and that they decrease all auditory input including the directed communication needed for…”
Section: Plos Onementioning
confidence: 99%
“…Earplugs may represent a choking hazard [13]. Improvements in weight gain due to a noise-attenuated environment have been demonstrated in randomized prospective studies of low birth weight hospitalized infants [13,39]. Adequate growth is a prerequisite of a successful discharge from the NICU.…”
Section: Plos Onementioning
confidence: 99%
“…Studies that used EPs to evaluate behavioral aspects, such as sleep, motor response, pain and physiological parameters like body temperature, oxygen saturation, blood pressure, and heart and respiratory rates in PTNs, performed the intervention for periods of two hours or more (13)(14)(15)(24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…These Newborns (NB), due to prematurity, are usually referred to the Neonatal Intensive Care Unit (NICU) (2) . Endowed with high technology and a massive supply of care, the NICU has a dual character since it favors clinical stability and survival (2) of premature newborns, while at the same time subjecting them to damages (3)(4) . One of the factors that makes them vulnerable is their insufficient capacity for selfregulation, due to the high sensorial loads experienced in this context (3) , mainly due to the effects of interventions performed without adequate measures of pain management (5) , luminosity and noise, allied to care protocols that disregard sleep and rest issues, generating stress and discomfort to the premature.…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors that makes them vulnerable is their insufficient capacity for selfregulation, due to the high sensorial loads experienced in this context (3) , mainly due to the effects of interventions performed without adequate measures of pain management (5) , luminosity and noise, allied to care protocols that disregard sleep and rest issues, generating stress and discomfort to the premature. Such context may imply an increased risk of abnormal brain maturation (4) and constitutes a morbidity factor (2) .…”
Section: Introductionmentioning
confidence: 99%